Testing mammary gland secretions to predict foaling in jennies - Tiziana Nervo; Alessia Bertero; Patrizia Ponzio; Eleonora Julita; Mariagrazia Lucia Poletto; Gian Guido Donato (Italian Journal of Animal Science)
The surging demand for donkey milk has led to a stronger focus on donkey husbandry and reproductive management, particularly in the peripartum period. Techniques to predict parturition are needed to avoid losses due to dystocias, which are frequently related to unattended foaling. In mares, pH and electrolyte analyses of pre-colostrum are used to predict parturition with a good accuracy. The purpose of this study was to evaluate the pH of the mammary secretion using both a pH metre and test strips and the electrolytes (Na+, K + and Ca2+) in the mammary gland secretions of 9 jennies during the 5 days preceding parturition, to understand if the trends of these cations were comparable to those of the mare and to identify possible markers/thresholds of impending parturition. Ca2+ concentrations increased in the days before delivery from day −2 (p < 0.01) and 78% of the jennies foaled within 48 h of reaching the threshold of 20 mmol/L. Na + and K + levels remained constant as parturition approached. The pH decreased in the days before foaling, starting from day −1 (p < 0.05). However, it was not possible to deduce certain indications on the date of delivery based on electrolyte concentrations, nor on pH and at the current state of knowledge foaling alert systems are the only methods for ensuring prompt assistance during parturition.Highlights The ability to predict parturition for providing adequate assistance is essential in a donkey farm. pH and electrolytes of mammary gland secretions are used in mares to predict foaling, but no reference values are available for jennies. In our work, neither electrolyte nor pH evaluations proved to be reliable to predict with an adequate level of confidence the impeding parturition.